Fenomena Kekerasan Seksual Terhadap Anak - La Ode Anhusadar; Rusni Rusni (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
Sexual violence is an important and complicated issue of violence against women all over the map because there is a dimension which is very typical for women. Relasikuasa inequality issues between the perpetrator and the victim are the roots of sexual violence against women. In such a case of sexual violence against women, inequality of power relations in question is between men and women. Inequality is exacerbated when one party (the perpetrators) have more control over the victim. This control can be resources, including knowledge, economy and public acceptance (social status / social modalities). It also includes controls that appear on the form of patron-client relationship or feudalism, such as the parent-child, employer-worker, teacher-student, community leaders-residents and armed groups / forces-the civilian population. Violence against children is everything that made the child tortured, both physically, psychologically mental maupu. Violence against children is an act of abuse or maltreatment of children in the form of physical abuse, emotional, sexual, neglect of care and exploitation for the benefit of commercial real or even not to harm the health, survival, dignity and development, violence derived from the responsible, trustworthy and powerful in the protection of the child. Keywords: Sexual Violence and Children